PENGARUH PEMBERIAN AROMATERAPI MINYAK MELATI (Jasminum sambac L.) TERHADAP PENURUNAN DERAJAT INSOMNIA PADA LANSIA DI BANJAR GEDE KELURAHAN SEMPIDI - Ni Putu Yuliana Assari; I Gusti Made Aman; Ida Ayu Manik Partha Sutema (Sekolah Tinggi Ilmu Kesehatan Samarinda, 2022)
The humans’ organs function will be decreased when humans are getting older. It caused they to had insomnia. Insomnia is a condition of humans’ sleeping problem. Jasmine oil aromatherapy is an essential oil which is used to decrease insomnia. The research aimed at knowing or prove that jasmine oil aromatherapy can reduce the degree of insomnia in the elderly. The research method was a quasy experimental one group pretest-posttest design. The research subject was 34 elderlies who were selected by the purposive sampling. The degree of insomnia before and after the intervention was measured using the Insomnia Severity Index (ISI) questionnaire. The test result of Friedman showed that there was differences in the degree of insomnia after giving jasmine oil aromatherapy to the elderly (p=0,001). Before giving jasmine oil aromatherapy, the average value was 19,147. Meanwhile, after using jasmine oil aromatherapy on the 8th day, the average value was 13,000 and on the 15th day there was a significant decrease in the degree of insomnia with an average value of 7,147. the administration of jasmine oil aromatherapy can significantly reduced the degree of insomnia in the elderly in Banjar Gede, Sempidi Village started on day 8 (2nd posttest) and day 15 (3rd posttest).